Relation of haemostatic function, neurovascular impairment, and vibration exposure in workers with different stages of vibration induced white finger. Issue 4 (April 1985) - Bovenzi, M; Giansante, C; Fiorito, A; Calabrese, S
Abstract : Haemostatic function and neurovascular symptoms were investigated in 67 workers exposed to vibration and 46 comparable referents. Of these 65.6% of vibration workers complained of neurological disturbances (stages 0T, 0N of Taylor's classification for vibration induced white finger (VWF) and 20.9% suffered from Raynaud's phenomenon (stages 1-2-3). The severity of the staging symptoms showed a close relation with an index of vibration dose computed on the basis of vibration measurement and individual exposure time. Indices of platelet aggregation, both in vitro and in vivo, antithrombin III, fibrinogen and fibrinopeptide A levels were not different in the exposed workers compared with the referents. No relation was found between haemostatic parameters and the severity of VWF. Exposed workers responded to a cooling procedure with a more pronounced vasoconstriction in the digital vessels than the referents, as indicated by delayed recovery time of finger skin temperature after the cold test. These findings suggest that both in the early stages (0T, 0N) and in more severe stages of VWF (stages 1-2) cold induced hyperreactivity in the digital vessels and Raynaud's syndrome are vascular disorders of functional origin occurring without any prethrombotic alterations.